Vấn đề thạch luận và tuổi hình thành các đá Gabroit cao kiềm trong khối Sơn Đầu và phía Tây Núi Chúa - Hùng, Trần Quốc; Poliyakov, G.V.; Shelepaev, P.A.; Hòa, Trần Trọng; Phượng, Ngô Thị; Balykin, P.A.; Izokh, A.E.; Niên, Bùi Ấn; Sukhorukov, P.V. (Vietnam Journal of Earth Sciences, 2012)
SUMMARY High alkali gabbroid of Son Dau massive and western part of Nui Chua Massive, Petrogenesis and forming age This article recommends present researched re-sults about high alkali gabbroids of Son Dau massive and western part of Nui Chua massive. Their petrogra-phic and geochemical characteristics are similar to monsogabbro and monsodiorite, while the age dating (SHRIMP from zircon in monzogabbro, 250.4 ±2 Ma, coeval to Nui Chua massive 251 ±3 Ma). The modeling of Nui Chua massive‘s forming process shows that Son Dau massive and its satellite at the western part of Nui Chua massive were generated from residual high alkalic magmatic liquids by fractional crystallization. The forming conditions are 750-840 °C and 2-3 kbar. In addition, this area has large ore deposit potential, because of high titanomagnetite and ilmenite content in monsogabbro and monsodiorite.